Bombyx mori epidermal growth factor receptor is required for nucleopolyhedrovirus replication. Issue 4 (30th March 2018) - Jin, S.; Cheng, T.; Guo, Y.; Lin, P.; Zhao, P.; Liu, C.; Kusakabe, T.; Xia, Q.
Abstract: Baculovirus–host interactions are important models for studying the biological control of lepidopteran pests. Research on baculovirus–host interactions has focussed on baculovirus manipulation of cellular signalling pathways, including the extracellular signal‐regulated kinase (ERK) and phosphatidylinositol‐3‐kinases/protein kinase B (PI3K/Akt) signalling pathways. However, the mechanism underlying ERK and PI3K/Akt activation and function in response to baculovirus infection remains poorly understood. Here, we demonstrated that baculovirus activated the Bombyx mori ERK and PI3K/Akt signalling pathways via the B. mori epidermal growth factor receptor (BmEGFR). To further characterize the function of the BmEGFR/ERK signalling pathway in baculovirus replication, we calculated genome‐wide changes in kinase–chromatin interactions for ERK after baculovirus infection using chromatin immunoprecipitation followed by high‐throughput sequencing. A Gene Ontology analysis showed that virus infection had effects on the biological regulation, cellular process and metabolic process pathways. Moreover, ERK was shown to regulate the transcription of late viral genes. Taken together, our results suggest that baculoviruses manipulate components of the host cell machinery for replication via modulation of the BmEGFR signalling pathway.